Daya Hambat Ekstrak Daun Mangrove Bruguiera gymnorrhiza Terhadap Pertumbuhan Candida Albicans pada Gigi Tiruan Lepasan Akrilik (e-GiGi, 2024)
Abstract: Rough surface and poorly kept denture, especially those facing the supporting mucosa, can become a reservoir for the growth of microorganisms, such as the Candida albicans. Natural ingredients are chosen for denture cleanser because they are relatively cheap and safe. The mangrove plant Bruguiera gymnorrhiza is a natural source which contains active compounds, including saponins, flavonoids, phenol hydroquinones, alkaloids, and tannins which are antioxidants, anti-inflammatory, antibacterial, antiviral, antifungal, hypoallergenic, etc. This study aimed to determine the inhibition of Bruguiera gymnorrhiza mangrove leaf extract on the growth of Candida albicans on removable denture plates and to determine the effective concentration that could inhibit the growth of Candida albicans. This was a true experimental laboratory study with a post test control group design. The test method used was the modified Kirby-Bauer method using wells. Samples were divided into four groups with respective concentrations of 20%, 30%, 40%, 50%, control positive, and control negative. The one-way ANOVA test showed a p-value of